Automated Market Makers - Mohsen Pourpouneh; Kurt Nielsen; Omri Ross (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
A new type of Automated Market Makers (AMMs) powered by Blockchain technology keep liquidity on-chain and offer transparent price mechanisms. This innovation is a significant step in the direction of building a more transparent and efficient financial market. This paper explores analytically market mechanisms and shows the conditions when those mechanisms are equivalent. Furthermore, we show that AMM mechanisms inherently create loses for market makers from inefficient prices (dictated by the AMM solutions), however, these mechanisms work well for assets with low volatility. We further analytically explore the losses and quantify them. The paper ends by discussing the design of efficient decentralized exchange compared to traditional Central Limited Order Books (CLOBs) and highlights the former's potential regarding decentralized finance.
Keywords: D53; G12; 330; blockchain; decentralized exchanges; automated liquidity providers; auction; mechanism design